INDONESIAN TIMBER LEGALITY ASSURANCE SYSTEM (SVLK): IN PURSUIT OF SUSTAINABILITY IN FOREST GOVERNANCE - Kadir, M. Yakub Aiyub (UI Scholars Hub, 2019)
This paper investigates the Indonesian Timber Legality Assurance (Sistem Verifikasi Legalitas Kayu, SVLK) and its nature to produce legal wood under the European Union-Forest Law Enforcement Governance and Trade (EU-FLEGT) system. It is intended to ensure the exporting states control over legality of wood under new forest governance and its enforcement in EU market. Using a critical legal analysis, this paper argued that the SVLK could present legality in a formalistic way, but it could not guarantee the substantial meaning of benefit for sustainability, participatory and community. Therefore this paper contributes to provide a better understanding of the application of SVLK in Indonesia, along with reflecting some recommendations, as developing SVLK for domestic market, and replicating it into other exporting natural resources products. The comprehensive approaches for enforcing SVLK can lead to accelerate sustainability in more practical and grounded sense, to improve forest governance and welfare for local people therein.